Agricultural wastes potential (pineapple crown, durian peel and sugarcane leaves) on reducing sugar production by using sulfuric acid pretreatment following enzymatic hydrolysis - Boonwong, Thirawan; Karnnasuta, Sujinna; Srinorakutara, Teerapatr (Asia-Pacific Journal of Science and Technology, 2017)
Studies are underway to use the potential of agricultural wastes (pineapple crown, durian peel and sugarcane leaves) for reducing sugar production by using sulfuric acid pretreatment following enzymatic hydrolysis. After pretreatment lignocellulosic feedstocks with 2.0%(w/v) sulfuric acid (H 2 SO 4 ) and autoclave at 121 o C pressure 15 lb/in 2 for 15 min, reducing sugar of the feedstock contained between 49.00-61.87 g/L, the pineapple crown had a high concentration (61.87+-0.59 g/L), durian peel (56.83?0.36 g/L) and sugarcane leaves (49.00ฑ1.14 g/L) respectively. When hydrolyzed the sulfuric acid pretreated feedstocks with 60 FPU/g (DS) cellulase enzyme (Cellic ? CTec2), the reducing sugar of pineapple crown was remained highest (113.70+-0.47 g/L), the second was durian peel (100.00?0.99 g/L) and sugarcane leaves (95.09+-1.54 g/L) respectively. Fermentation of reducing sugar solution of hydrolysate pineapple crown by Saccharomyces cerevisiaeTISTR 5596 found to be maximal ethanol 33.58+-1.96 g/L or 4.3%(v/v) at 72 hours, which equal 230.81 kg/ton (DW).